2023
DOI: 10.3390/v15051129
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron Specific Mutations Affecting Infectivity, Fusogenicity, and Partial TMPRSS2-Independency

Abstract: The COVID-19 pandemic resulted from the global spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since its first appearance in 2019, new SARS-CoV-2 variants of concern (VOCs) have emerged frequently, changing the infection’s dynamic. SARS-CoV-2 infects cells via two distinct entry routes; receptor-mediated endocytosis or membrane fusion, depending on the absence or presence of transmembrane serine protease 2 (TMPRSS2), respectively. In laboratory conditions, the Omicron SARS-CoV-2 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Omicron exhibits reduced TMPRSS2-dependency, enabling infection of TMPRSS2-positive cells through both entry pathways, facilitated by the presence of Omicron-specific Spike Y655 residue ( Figure 5 a). However, the precise underlining mechanism remains elusive [ 13 , 24 , 40 ]. To investigate whether the diminished Omicrons reduced TMPRSS2-dependency might stem from a decreased binding between Omicron-Spike and TMPRSS2 due to the Y655 residue, HEK293T were transfected with Omicron-Spike wt and Y655H mutant, along with a reciprocal experiment involving Delta-Spike wt and H655Y.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Omicron exhibits reduced TMPRSS2-dependency, enabling infection of TMPRSS2-positive cells through both entry pathways, facilitated by the presence of Omicron-specific Spike Y655 residue ( Figure 5 a). However, the precise underlining mechanism remains elusive [ 13 , 24 , 40 ]. To investigate whether the diminished Omicrons reduced TMPRSS2-dependency might stem from a decreased binding between Omicron-Spike and TMPRSS2 due to the Y655 residue, HEK293T were transfected with Omicron-Spike wt and Y655H mutant, along with a reciprocal experiment involving Delta-Spike wt and H655Y.…”
Section: Resultsmentioning
confidence: 99%
“…A mediator of TMPRSS2 interaction with SARS-CoV-2 Spike protein is the H655 residue. The observation that Omicron infection is only partially dependent on TMPRSS2 might be explained by the weakened TMPRSS2 interaction due to the Omicron Spike Y655 residue [ 13 , 24 , 53 ]. Considering the observed correlation between TMPRSS2 affinity for Spike and the infection pathway via the cell membrane, we hypothesize that the physical interaction between these two proteins reduces the utilization of the endosomal route for SARS-CoV-2 Spike-mediated entry ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spike protein in Omicron strains may be less sensitive to the action of transmembrane serine proteases, notably TMPRSS2, TMPRSS11d, and TMPRSS13, due to mutations, and their fusogenic capacities therefore appear impaired [137][138][139]. Studies tend to show that Omicron variants prefer the endosomal entry route to that of the fusion at the plasma membrane [139,140], although the independence of their Spike protein from TTSPs may be questioned, particularly for BA.2.86 [141,142].…”
Section: Is the Spike Protein Of Omicron Variants Less Dangerous?mentioning
confidence: 99%
“…It has been demonstrated that SARS-CoV-2 can use both Cathepsin B/L and TMPRSS2 for cell entry, particularly in human lung cells. Otherwise, the omicron variant of SARS-CoV-2 enters cells by endo/lysosomal cysteine protease Cathepsin L [44].…”
Section: Mechanisms Of Virus Entrymentioning
confidence: 99%